2018
DOI: 10.1111/jsr.12761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous positive airway pressure on neurocognitive and neuropsychiatric function in obstructive sleep apnea

Abstract: The aim of this study was to determine the neurocognitive and neuropsychiatric effects of continuous positive airway pressure treatment on patients with obstructive sleep apnea. This cross‐sectional, prospective, observational study included 126 patients with sleep apnea. The following tests were performed: the Montreal Cognitive Assessment for the evaluation of cognitive impairment, the Beck Depression Inventory, and the State‐Trait Anxiety Inventory, together with the Epworth Sleepiness Scale for the evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…A beneficial effect of short-term (2-3 months) treatment following CPAP on EDS (48, 50, 52-58) and depression (37,48,50,52,55,56,58) has been seen in many studies. Both somatic and affective/cognitive symptoms on the Beck Depression Inventory (BDI) improved equally after 3 months' CPAP treatment for OSA (37).…”
Section: Short-term (2-3 Months) Treatmentmentioning
confidence: 98%
“…A beneficial effect of short-term (2-3 months) treatment following CPAP on EDS (48, 50, 52-58) and depression (37,48,50,52,55,56,58) has been seen in many studies. Both somatic and affective/cognitive symptoms on the Beck Depression Inventory (BDI) improved equally after 3 months' CPAP treatment for OSA (37).…”
Section: Short-term (2-3 Months) Treatmentmentioning
confidence: 98%
“…The purpose of this study was to assess the effects of nocturnal CPAP breathing on the emotional status and cognitive performance in OSA patients. A total of 21 articles were reviewed for this study [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. To find, screen, and choose relevant publications, we used PubMed, PubMed Central (PMC), and MEDLINE as our primary databases.…”
Section: Reviewmentioning
confidence: 99%
“…We ensured to include studies that measured the effect of CPAP on depression and anxiety by using any one of the validated scales such as the Beck Depression Inventory (BDI), the State-Trait Anxiety Inventory (STAI), Hospital Anxiety and Depression Scale (HADS), or Hamilton Depression Scale (HAM-D). Five observational studies found that CPAP improves OSA's psychological complaints when used over three months [20][21][22][23][24]. One study even finds it to be more effective in improving depressive symptoms than surgical treatment [20].…”
Section: Effect Of Cpap On Depression Anxiety and Quality Of Life In Osa Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Validated modifiable risk factors can be used to mitigate the progression of age-related cognitive decline. For instance, OSAS is associated with Alzheimer's disease biomarker accumulation (Bubu et al, 2019) and can be treated with continuous positive airway pressure (CPAP) (Marshall et al, 2006;Cooke et al, 2009;Kylstra et al, 2013;Richards et al, 2019), which improves cognitive function in patients suffering from Alzheimer's disease, although its effect on pathological progression remains unknown (Ancoli-Israel et al, 2008;Troussiere et al, 2014;Dostalova et al, 2019). The purpose of this exploratory study was therefore to (a) assess the prevalence of each form of SAS in a cohort of elderly patients (>70 years old) admitted to our geriatric unit for non-acute reasons, and (b) investigate the independent relation between sleep apnea and cognitive performance, measured using validated tests, including the Mini Mental-State Exam (MMSE), the Mattis Dementia rating Scale (MDRS) and the Stroop test, and competing against known risk factors for cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%